The use of role play for improving the speaking skill of the english language among 10th year students at Adolfo Jurado González public school, academic period 2013-2014 - Hurtado Vargas, Gabriela Estefania (2015)
This action research study had the purpose to improve the speaking skill through the use of role play. The research was conducted at ¨Adolfo Jurado Gonzalez¨ Public School; the participants of the research were the tenth year students. The intervention plan of six sessions was carried out to improve the speaking skill using role play. Two researcher-made tests and questionnaires were designed and used to measure the eleven students’ progress and perception of the use of role play. Additionally, instruments like checklists and learning logs were also used every session to check the students’ growth. The results indicated that the use of role play facilitated meaningfully the improvement of the speaking skill which was reflected in the noticeable increase of the posttest scores and students’ progress during the intervention. The conclusion that can be drawn from these facts is that this study helped the students to improve their speaking skill.